Comparison of early pregnancy serum concentration of neopterin, neopterin/creatinine ratio, C‑reactive protein, and chitotriosidase, in pregnant women with birth at term and spontaneous preterm birth - Navolan, Dan Bogdan; Stoian, Dana Liana; Bohiltea, Roxana Elena; Crainiceanu, Zorin; Craina, Marius Lucian; Cretu, Octavian; Timar, Bogdan; Vladareanu, Radu; Terness, Peter; Bürger, Friederike; Nemescu, Dragos (Experimental and Therapeutic Medicine, 2020)
Inflammatory mechanisms are involved in achieving a normal pregnancy and in the development of certain pregnancy complications. These changes are more intense in pregnant women that suffer of pregnancy complications, such as spontaneous preterm birth (SPB). This study compared the course of inflammatory markers (IM) [neopterin (Neo), neopterin/creatinine ratio (Neo/Cre), C‑reactive protein (CRP), and chitotriosidase (Chito)] serum concentration in the early pregnancy of women with birth at term (BT) and preterm birth (PB). IM concentration was measured in 90 sera sampled from 45 pregnancies with BT and 30 sera from 15 pregnancies with PB. Two sera were sampled from each pregnant woman: one in the first trimester and another one in the second trimester. Early pregnancy IM concentration showed a direct correlation with gestational age: Neo (rho=0.262, P=0.004), Neo/Cre (rho=0.372, P<0.001), CRP (rho=0.187, P=0.041), and Chito (rho=0.039, P=0.66). The correlation was present in both categories of patients with BT and PB. Patients with PB before 34 week of pregnancy (wp) and 32 wp showed higher Neo and Neo/Cre concentration than BT patients. A significant association was found between the risk of PB before 34 wp, PB before 32 wp, and Neo concentration (PB <34 wp: odds ratio (OR) =5.13, P=0.035) (PB <32 wp: OR=8.2, P=0.020) and, respectively, Neo/Cre concentration (PB <34 wp: OR=5.29, P=0.015) (PB <32 wp: OR=9.25, P=0.006). No association between CRP or Chito and PB age was found. IM concentration correlates with the gestational age at the time of blood sampling. Increased Neo and Neo/Cre concentration are associated with PB. Further studies are needed to evaluate the usefulness of these markers in clinical practice.
Gesehen am 15.10.2020